Aplikasi Pupuk Hayati dan Pupuk Organik terhadap C-organik dan Derajat Infeksi Akar Tanaman Buah Naga (Hylocereus costaricencis L.) pada Tanah Pasir Bekas Tambang - Kiki Zakiah; Anni Yuniarti; Anne Nurbaity; Hidayat Salim (Soilrens, 2014)
Sand-mining can damage to physical, chemical and biological soil properties. Land reclamation is one of method that can be use to solved that problem. Adding soil ameliorant and revegatation are known can improve soil productivity. The objective of this study was to determine the effect of soil ameliorant, which is organic fertilizer and biofertilizer in improving soil organic-C and root infection of dragon fruit (Hylocereus costaricencis L.) by AMF on soil originated from Sand Mining, Sumedang, Indonesia. Greenhouse experiment was conducted at Faculty of Agriculture, Universitas Padjadjaran from December until June 2013. The experiment used was Factorial Randomized Block Design consist of two factors and three replications. The first factor was biofertilizer which consist of: without biofertilizer, AMF and AMF + MHB (Mychorriza Helper Bacteria). The second factor was organic fertilizer that consist of: without organic fertilizer, chicken manure, goat manure, cow manure, rabbit manure, cocopeat and Organic Granule Fertilizer (each 5 kg / pot). Results of experiment showed that there was interaction effect between organic fertilizer and biofertilizer in improving soil organic-C. There was no interaction effect between organic fertilizer and biofertilizer to root infection.